The impact of Digital Transformation on the quality of Higher Education (Case study The Faculty of Economics, Commerce, and Management in Amar Thelidji University- Laghouat) - Dahbi , assia; Bouhali , mohamed (Dirassat Journal Economic Issue, 2024)
The objective of this study is to determine the impact of digital transformation on the quality of higher education as perceived by professors at the Faculty of Economic, Commercial and Management Sciences, University of Ammar Thliji Laghouat. The study examines the independent variable of digital transformation, which encompasses four dimensions: strategy, organizational culture, transformational leadership, and human resources. The dependent variable in this study is the quality of higher education. In order to accomplish the study’s objectives, data collection was conducted through the utilization of a questionnaire. The sample size consisted of 56 individuals, and their data was subsequently analyzed using various statistical indicators via the SPSS26 program. The research findings indicate that there is no statistically significant impact of digital transformation on the quality of higher education, as observed within the examined sample.